MOTIVASI BERPRESTASI DENGAN KREATIVITAS PESERTA DIDIK KELAS X SEKOLAH MENENGAH ATAS NEGERI 1 PEMANGKAT - Efendi, Zulham; Purwanti, Purwanti; Yusuf, Abas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is how the correlation between achievement motivations with creativity of students on X Grade Students in Senior High School 1 Pemangkat is. The purpose of this research is to get information about Correlation Between Achievement Motivation with Creativity on X Grade Students of Senior High School 1 Pemangkat. The method used in this research is quantitative research. In this study, the author used correlational design research in forms or Correlational Design. The population in this study are students of SMAN Pemangkat as many as 152 students, with this sample 30 learners. The data analysis used is correlation analysis. The results showed Characteristics of achievement motivation level on X grade students in Senior High School 1 Pemangkat in Sambas regency is categored as very good which is 84.02%. Characteristics of the level of creativity of learners of X grade students in senior high school 1 Pemangkat is categorized very good which is 84.41%. Result of correlation test of r-test bigger r-table or 0,795> 0,05 mean there is accorrelation between achievement motivation with creativity of student of X grade students in Senior High School 1 Pemangkat. The relation is very strong.Keywords: Achievement Motivation, Students’ Creativity